2011
DOI: 10.1097/nna.0b013e3182378d53
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Fall

Abstract: : The data offer a hopeful perspective on the role of nursing engagement in developing a hospital-wide culture of safety and protecting patients from permanent harm caused by fall events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The rate of falls (12.9% vs 12.2%) did not change significantly during the three-month post-intervention data collection period compared to the three-month pre-intervention period. In contrast, significant reductions in falls were reported by Johnson et al [40] with an intervention focussing on falls education for patients and nurses. Across the three-year period which included baseline assessment and intervention, the yearly fall rate reported by Johnson et al [40] in a general hospital ward decreased from 3.5 to 2.3%.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The rate of falls (12.9% vs 12.2%) did not change significantly during the three-month post-intervention data collection period compared to the three-month pre-intervention period. In contrast, significant reductions in falls were reported by Johnson et al [40] with an intervention focussing on falls education for patients and nurses. Across the three-year period which included baseline assessment and intervention, the yearly fall rate reported by Johnson et al [40] in a general hospital ward decreased from 3.5 to 2.3%.…”
Section: Resultsmentioning
confidence: 87%
“…All included studies reported on hospital patients in a variety of settings including acute care [19] [20] [21] [3] [22], geriatric wards [23] [24] [25] [26], surgical units [27], orthopaedic wards or hospital [28] [29] [30], stroke rehabilitation ward [31], post-natal ward [32], psychiatric in-patient ward [33], long term care [34], oncology [35] and general hospital wards [36] [37] [38] [39] [40] [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaders attribute their collective success to shared governance, open communication, mutual trust and respect, and an unwavering commitment to quality patient care and continuous improvement. They have also leveraged this convergence successfully to achieve significant improvements in nursing outcomes at our hospital, most recently in reducing falls (Johnson et al., ). They established a highly respected brand for nursing at RWUJH—one that survived and thrived through numerous union strikes and has achieved multiple re‐certifications as a Magnet institution.…”
Section: Where Unions and Magnet Meetmentioning
confidence: 99%
“…In the United States falls cause 45% of unintentional trauma-related mortality; this is even higher for women (CDC, 2011;WHOE 2005). Falls in people above the age of 65 years are of special concern since only 50% of these seniors will live more than a year after sustaining a fall (Johnson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%